Clinical Utility of the Nonstructural 1 Antigen Rapid Diagnostic Test in the Management of Dengue in Returning Travelers With Fever. (9th January 2017) - Huits, Ralph; Soentjens, Patrick; Maniewski-Kelner, Ula; Theunissen, Caroline; Van Den Broucke, Steven; Florence, Eric; Clerinx, Jan; Vlieghe, Erika; Jacobs, Jan; Cnops, Lieselotte; Van Den Bossche, Dorien; Van Esbroeck, Marjan; et al.
Abstract: Background: Rapid diagnostic test (RDT) detecting the nonstructural 1 (NS1) antigen is increasingly used for dengue diagnosis in endemic and nonendemic settings, but its clinical utility has not been studied in travel clinic practice. Methods: From August 2012 to July 2016, travelers returning from the tropics with fever were evaluated in the Institute of Tropical Medicine (Antwerp, Belgium) with the routine use of NS1 antigen RDT that provided results within 1 hour. We determined the diagnostic performance, assessed the management of patients with a positive RDT result, and compared it with that of historical cases of dengue diagnosed from 2000 to 2006, when only antibody detection assays were available. Results: Of 335 travelers evaluated for fever, 54 (16%) were diagnosed with dengue, including 1 severe case. Nonstructural 1 antigen RDT was performed in 308 patients. It was truly positive in 43 of 52 tested dengue cases and falsely positive in only 1 of the 256 nondengue cases; therefore, sensitivity was 82.7% (95% confidence interval [CI], 74.4%–93.0%) and specificity was 99.6% (95% CI, 98.8%–100%). Only 3 (7%) of the 43 febrile travelers "immediately" diagnosed by RDT were admitted, and only 2 (5%) were given empirical antibacterial treatment, without adverse outcome. Admission and antibiotic prescription rates were significantly higher in the historical cases (n = 43) diagnosed by antibody detection (33%, P = .006 and 26%, P = .014, respectively), although the frequency of severe dengue was similar. Conclusions: In our practice, the diagnostic performance of NS1 antigen RDT substantially contributed in withholding unnecessary hospitalization and antibiotherapy in dengue patients.